Comportamento de cultivares precoces de feijão (Phaseolus vulgaris L.) no estado de Minas Gerais - A de Andrade Araújo, Geraldo; Vieira, Clibas; Costa, Carlos Roberto; de Oliveira, Flávio; Souza Lima, Carlos Alberto; Faria Vieira, Rogério; Chagas, José Mauro (Revista Ceres, 2025)
The following early-maturing field bean cultivars were included in ten yield trials, at six localities in Minas Gerais State, Brazil: Vermelho Rajado 977, Col. 1-63-A, Bolinha 1201, Palmital Precoce, BAT 304, Batatinha, CNF 10, Jalo CNF 243, Mineiro Precoce 1913, Dark Red Kidney CNF 252, Jalinho CNF 255, Jalo CNF 260, Enxofre CNF 261, Preto CNF 266, 3556 DOR-196, 3594, Eriparsa I, EEP 543/75, 3595 DOR-95, and Preto Sessenta Dias 1964.